Effects of antioxidant supplementation on the aging process - Domenico Fusco (Dove Medical Press, 2007)
Domenico Fusco1, Giuseppe Colloca1, Maria Rita Lo Monaco1, Matteo Cesari1,21Department of Gerontology, Geriatrics and Physiatry; Catholic University of Sacred Heart, Rome, Italy; 2Department of Aging and Geriatric Research, College of Medicine, Institute on Aging, University of Florida, Gainesville, FLAbstract: The free radical theory of aging hypothesizes that oxygen-derived free radicals are responsible for the age-related damage at the cellular and tissue levels. In a normal situation, a balanced-equilibrium exists among oxidants, antioxidants and biomolecules. Excess generation of free radicals may overwhelm natural cellular antioxidant defences leading to oxidation and further contributing to cellular functional impairment. The identification of free radical reactions as promoters of the aging process implies that interventions aimed at limiting or inhibiting them should be able to reduce the rate of formation of aging changes with a consequent reduction of the aging rate and disease pathogenesis. Even if antioxidant supplementation is receiving growing attention and is increasingly adopted in Western countries, supporting evidence is still scarce and equivocal. Major limitations in literature are still needed to be addressed to better evaluate the potential benefits from antioxidant supplementation: 1) an improved understanding of oxidation mechanisms possibly at the basis of the aging process, 2) the determination of reliable markers of oxidative damage and antioxidant status, 3) the identification of a therapeutic window in which an eventual antioxidant supplementation may be beneficial, 4) a deeper knowledge of the antioxidant molecules which in several conditions act as pro-oxidants. In the present paper, after a preliminary introduction to the free radical theory of aging and the rationale of antioxidant supplementation as an anti-aging intervention, we will present an overview of evidence relating antioxidant supplementations with clinical conditions typical of older age (ie, cardiovascular disease, Alzheimer’s disease, cancer). We will also discuss studies that have evaluated whether antioxidant supplementation might improve major outcomes of interest in older persons (ie, physical performance, muscle strength, longevity). Given the large amount of data available on the antioxidant supplementation topic, this overview is not intended to be exhaustive. The aim of this paper is to provide the main basis from which future studies should start and indicate which the main limitations that need to be addressed are.Keywords: aging, anti-aging medicine, antioxidant supplementation, oxidative damage